Loss of Amazonian Forests due to Urban Expansion in Peru - Moschella, Paola (2023)
The occupation of peri-urban areas in the eight largest Amazonian cities is studied, along with its impact on forest conservation, in order to identify conditions associated with greater or lesser loss of peri-urban forests. For this purpose, a comparative analysis of demographic and spatial indicators is conducted, as well as a spatial analysis of recent urban growth over forested areas. Furthermore, challenges for the conservation of peri-urban forests are discussed based on key territorial dynamics and existing mechanisms for territorial planning and management. It is identified that the greater pressure from urban growth on peri-urban forests is mainly linked to migratory processes and regional economic dynamics related to mining and tourism activities. Likewise, the trend towards reduced population and housing density in new expansion areas, along with an increase in the real estate supply for secondary residences, poses a threat to sustainability. Peri-urban roads concentrate deforestation areas and future urban expansion, highlighting the need to enhance mechanisms for environmental impact assessment of road infrastructure and focus efforts on sustainable land management measures in these zones.